Spatial patterns of parasitism of the solitary parasitoid pseudapanteles dignus (Hymenoptera: Braconidae) on Tuta absolute (Lepidoptera: Gelechiidae) - Sanchez, Norma Elba (2009)
We examined the interaction between the tomato leafminer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), a key pest of tomato crops in South America, and its main solitary larval parasitoid, Pseudapanteles dignus (Muesebeck) (Hymenoptera: Braconidae). The pattern of parasitism of T. absoluta by the parasitoid was studied at three scales on tomato crops: plant, leaf, and leaflet. Host density, spatial distributions of both host and parasitoid, percentages of parasitism, variation in the probability and risk of parasitism in relation to host density, and the spatial density dependence were assessed in a horticultural region in Argentina. The spatial distribution of T. absoluta was clumped at all sites and scales, whereas that of P. dignus was much more variable, fitting to negative, positive binomial distributions and to Poisson series. Percentages of parasitism were as follows: site 1,17.06%; site 2,27.53%; site 3,26.47%; site 4,45.95%. Parasitoid aggregation in relation to host density was found at leaf and leaflet scales. However, the proportion of parasitized hosts was independent of host density. The variability of parasitism rates exhibited at the three spatial scales seems to result in partial refuges for the host, which might contribute to the persistence of the interaction between host and parasitoid. We discuss our field observations in relation to ecological theory and its potential application to the biological control of T. absoluta on tomato. © 2009 Entomological Society of America.